(untitled) - Lenka Štureková; Elena Gurková; Daniel Šaňák (University of Ostrava, 2024)
Aim: To describe current scientific knowledge on cognitive impairment and emotional disturbances (anxiety and depression) in younger adult patients after ischemic stroke. Design: A scoping review. Methods: For the search, the following scientific databases were utilized: Web of Science, MEDLINE (Ovid), ScienceDirect (Elsevier), PsycInfo (EBSCO), Scopus (Elsevier), and ProQuest. Relevant studies were identified by searching publications from 2000 to July 2023. Results: A total of eight studies were ultimately included in the review. Cognitive impairment occurred in a range between 39.4% and 40%. This encompassed various aspects of cognitive function, such as working memory, processing speed, global cognitive function, immediate and delayed memory, attention, and executive functioning. Depression had an incidence rate ranging from 10.8% to 16.8%. Several risk factors were associated with a higher likelihood of developing generalized anxiety. These included younger age, more depressive symptoms, lower education, unemployment, a history of depression, and alcohol use. In the context of depressive symptoms, a higher risk was linked to lower education and unemployment. Conclusion: The included studies highlighted the need to assess these issues not only at the time of patient discharge but, more importantly, during the stage of further recovery. This can contribute to the creation of tailored interventions for these individuals.